INOVASI PEMBELAJARAN FIQIH BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENCEGAH PERILAKU PINJAMAN ONLINE SISWA KELAS XI MA - Mukhamd Nabil Humaidi Syaputra; Saifullah Saifullah; Anang sholikhudin; Ahmad Marzuki (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze the implementation of Contextual Teaching and Learning (CTL)-based learning in Fiqh subjects as an effort to prevent online loan behavior among eleventh-grade students at MA Miftakhul Huda Cendono. This research was motivated by the increasing use of online loans among adolescents, influenced by low financial literacy, the rapid development of digital technology, and students’ limited understanding of Islamic economic principles. Fiqh learning, which has generally been theoretical in nature, has not fully connected learning materials with students’ real-life experiences, particularly regarding digital economic practices and the dangers of usury-based online loans. This study employed a qualitative approach with a descriptive research design. Data collection techniques included observation, interviews, and documentation. Data analysis used the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of the CTL approach in Fiqh learning improved students’ understanding of the dangers of online loans, usury practices, and the importance of financial management based on Islamic principles. Contextual learning also encouraged students to become more active, critical, and reflective in understanding economic issues developing in society. In addition, the CTL approach helped students connect Fiqh materials with real-life experiences, making learning more meaningful and easier to understand. Therefore, CTL-based Fiqh learning can serve as a relevant and effective learning strategy in strengthening sharia financial literacy, building Islamic economic awareness, and shaping students’ character in responding wisely to the development of the digital economy in the modern era. ABSTRAK Penelitian ini bertujuan untuk menganalisis penerapan pembelajaran berbasis Contextual Teaching and Learning (CTL) pada mata pelajaran Fiqih sebagai upaya mencegah perilaku pinjaman online pada siswa kelas XI MA Miftakhul Huda Cendono. Penelitian ini dilatarbelakangi oleh meningkatnya penggunaan pinjaman online di kalangan remaja yang dipengaruhi oleh rendahnya literasi keuangan, perkembangan teknologi digital, serta kurangnya pemahaman peserta didik mengenai prinsip muamalah dalam Islam. Pembelajaran Fiqih yang selama ini cenderung bersifat teoritis dinilai belum sepenuhnya mampu menghubungkan materi pembelajaran dengan realitas kehidupan sehari-hari siswa, khususnya terkait praktik ekonomi digital dan bahaya pinjaman online berbasis riba. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan pendekatan CTL dalam pembelajaran Fiqih mampu meningkatkan pemahaman siswa mengenai bahaya pinjaman online, unsur riba, serta pentingnya pengelolaan keuangan yang sesuai dengan syariat Islam. Pembelajaran kontekstual juga mendorong siswa menjadi lebih aktif, kritis, dan reflektif dalam memahami permasalahan ekonomi yang berkembang di lingkungan masyarakat. Selain itu, penerapan CTL membantu peserta didik menghubungkan materi Fiqih dengan pengalaman nyata sehingga pembelajaran menjadi lebih bermakna dan mudah dipahami. Dengan demikian, pembelajaran Fiqih berbasis CTL dapat menjadi strategi pembelajaran yang relevan dan efektif dalam memperkuat literasi keuangan syariah, membangun kesadaran ekonomi Islami, serta membentuk karakter peserta didik yang bijak dalam menghadapi perkembangan ekonomi digital di era modern.